Transformasi Digital Dalam Tata Kelola Penanggulangan dan Mitigasi Bencana Melalui Implementasi Aplikasi SI-GABAN oleh BPBD Kabupaten Bondowoso - Avella Lincha Angjesta; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study is motivated by the need for fast, accurate, and integrated disaster governance in Bondowoso Regency, an area vulnerable to flash floods, landslides, strong winds, forest and land fires, and other disaster risks. The Regional Disaster Management Agency (BPBD) of Bondowoso Regency developed the SI-GABAN application as an e-government innovation to strengthen disaster reporting, mitigation information, disaster-prone area mapping, and disaster response coordination. This study aims to analyze the implementation of SI-GABAN in supporting disaster management and mitigation and to identify its supporting and inhibiting factors. This research uses a qualitative method with a descriptive approach through interviews, observation, documentation, and literature study. The analysis applies Clay G. Wescott's e-government theory, consisting of operational efficiency, transparency and accountability, service accessibility, and public participation, supported by Nick Carter's disaster management concept. The findings show that SI-GABAN supports the digitalization of disaster public services through real-time reporting, disaster-prone maps, mitigation information, weather and earthquake information, disaster news, and annual data features. The application helps BPBD accelerate coordination, data management, and decision-making while improving public access to disaster information. However, its implementation is not yet optimal due to uneven socialization, low use of reporting features, limited development budget, and unstable internet connectivity in some disaster-prone areas. This study concludes that SI-GABAN is reasonably successful as a disaster e-government instrument, but it requires stronger outreach, digital infrastructure, community participation, and sustainable budget support.